2015
DOI: 10.1111/sode.12131
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Child Interaction as a Cradle of Theory of Mind: The Role of Maternal Emotional Availability

Abstract: The present longitudinal study investigated the relative importance of emotional availability (EA) in 56 mother–child dyads when the child was 7 months and four‐year old as predictors of child's Theory of Mind at 4 years while controlling for early maternal mind‐mindedness (MM). Dyadic EA at 7 months predicted the child's Theory of Mind, even when controlling for child temperamental and cognitive characteristics as well as dyadic EA at 4 years and early maternal MM. Results indicate the specific importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 54 publications
(77 reference statements)
1
30
1
2
Order By: Relevance
“…Findings that the group of mothers who made at least one non-attuned comment were less emotionally available are consistent with reports from Meins et al (2012) that non-attuned comments in infancy are discriminating in predicting insecure attachment in toddlers, and preschool aged children . The only other researchers who have used the EAS to assess maternal behavior in relation to mindmindedness found no concurrent associations between non-attuned comments and EA at infant age 7 months (Licata et al, 2014), in contrast to our findings; however, nonattuned mind-related comments in infancy predicted more intrusive behavior at a 886 MCMAHON & NEWEY preschool follow-up, assessed again with the EAS (Licata, Kristen, & Sodian, 2016). Taken together, findings from these prospective studies suggest that non-attuned comments may be salient markers of non-optimal parenting behavior in infancy that can have lasting consequences for the parent-child relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings that the group of mothers who made at least one non-attuned comment were less emotionally available are consistent with reports from Meins et al (2012) that non-attuned comments in infancy are discriminating in predicting insecure attachment in toddlers, and preschool aged children . The only other researchers who have used the EAS to assess maternal behavior in relation to mindmindedness found no concurrent associations between non-attuned comments and EA at infant age 7 months (Licata et al, 2014), in contrast to our findings; however, nonattuned mind-related comments in infancy predicted more intrusive behavior at a 886 MCMAHON & NEWEY preschool follow-up, assessed again with the EAS (Licata, Kristen, & Sodian, 2016). Taken together, findings from these prospective studies suggest that non-attuned comments may be salient markers of non-optimal parenting behavior in infancy that can have lasting consequences for the parent-child relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…Structuring refers to the ability of the mother to scaffold appropriate interactions with her infant in a way that the infant responds positively . Structuring has been shown to be positively associated with the ability of an infant to encode actions as goal‐directed and theory‐of‐mind capacities . Evidence from a task‐based functional connectivity study suggests that greater functional connectivity between the amygdala and other maternal brain regions is associated with positive maternal behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…18 Structuring has been shown to be positively associated with the ability of an infant to encode actions as goal-directed and theory-of-mind capacities. 21 Evidence from a task-based functional connectivity study suggests that greater functional connectivity between the amygdala and other maternal brain regions is associated with positive maternal behaviours. In a study of women in the postpartum period, the association between taskbased functional connectivity while mothers viewed a video of their infant and maternal behaviours was examined.…”
mentioning
confidence: 99%
“…In contrast, children with high levels of negative affect in the parent-child relationship had lower levels of self-regulation, which can put them at risk for problems in social, emotional, and cognitive development. Similarly, Licata et al (2016) found that high levels of emotional connectedness between mothers and infants at 7 months predicted levels of theory of mind at 4 years of age. Furthermore, Feldman (2007) found that higher levels of synchrony in mother-child interactions at 3 and 9 months of life predicted capacity for empathy during adolescence.…”
Section: Quality Of Mother-child Interactionsmentioning
confidence: 85%